Development and validation of a stability-indicative agar diffusion assay to determine the potency of flucloxacillin sodium in capsules - Fiorentino, Flávia Angélica Masquio [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (My University, 2012)
Flucloxacillin sodium (FLU) is a semi-synthetic penicillin active against many gram-positive bacteria such as streptococci and penicilinase-producing staphylococci, including methicillin-susceptible S. aureus. This study describes the development and validation of a microbiological assay, applying the diffusion agar method for the determination of FLU, as well as the evaluation of the ability of the method in determining the stability of FLU in capsules against acidic and basic hydrolysis, photolytic and oxidative degradations, using S. aureus ATCC 25923 as micro-organism test and 3 x 3 parallel line assay design (three doses of the standard and three doses of the sample in each plate), with six plates for each assay, according to the Brazilian Pharmacopoeia. The validation method showed good results including linearity, precision, accuracy, robustness and selectivity. The assay is based on the inhibitory effect of FLU using Staphylococcus aureus ATCC 25923. The results of the assay were treated by analysis of variance (ANOVA) and were found to be linear (r = 0.9997) in the range from 1.5 to 6.0 μg/mL, precise (repeatability: R.S.D. = 1.63 and intermediate precision: R.S.D. = 1.64) and accurate (98.96%). FLU solution (from the capsules) exposed to direct UVC light (254 nm), alkaline and acid hydrolysis and hydrogen peroxide causing oxidation were used to evaluate the specificity of the bioassay. Comparison of bioassay and liquid chromatography by ANOVA showed no difference between methodologies. The results demonstrated the validity of the proposed bioassay, which is a simple and useful alternative methodology for FLU determination in routine quality control.
Keywords: Flucloxacillin; Bioassay; Penicillin; Pharmaceutical formulation; Quality control; Validation